2012
DOI: 10.1186/1471-2229-12-190
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis and binding affinity of tomato ethylene response factors provide insight on the molecular bases of plant differential responses to ethylene

Abstract: BackgroundThe phytohormone ethylene is involved in a wide range of developmental processes and in mediating plant responses to biotic and abiotic stresses. Ethylene signalling acts via a linear transduction pathway leading to the activation of Ethylene Response Factor genes (ERF) which represent one of the largest gene families of plant transcription factors. How an apparently simple signalling pathway can account for the complex and widely diverse plant responses to ethylene remains yet an unanswered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
151
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 68 publications
2
151
0
3
Order By: Relevance
“…Taking advantage of the recent release of the complete annotated tomato genome sequence (Tomato Genome Consortium, 2012), 77 tomato ERF genes were identified, but knowledge of their physiological significance has been hampered by the functional redundancy among members of this vast gene family. A number of the ERF genes identified in tomato are ethylene inducible and show a ripeningrelated expression pattern that highlights their putative role in fruit ripening (Sharma et al, 2010;Pirrello et al, 2012;Liu et al, 2014Liu et al, , 2015. Consistent with this hypothesis, tomato LeERF1 was reported to mediate the ethylene response, and its overexpression resulted in a constitutive ethylene response and accelerated fruit ripening and softening (Li et al, 2007).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Taking advantage of the recent release of the complete annotated tomato genome sequence (Tomato Genome Consortium, 2012), 77 tomato ERF genes were identified, but knowledge of their physiological significance has been hampered by the functional redundancy among members of this vast gene family. A number of the ERF genes identified in tomato are ethylene inducible and show a ripeningrelated expression pattern that highlights their putative role in fruit ripening (Sharma et al, 2010;Pirrello et al, 2012;Liu et al, 2014Liu et al, , 2015. Consistent with this hypothesis, tomato LeERF1 was reported to mediate the ethylene response, and its overexpression resulted in a constitutive ethylene response and accelerated fruit ripening and softening (Li et al, 2007).…”
supporting
confidence: 56%
“…Because they are encoded by a large multigene family, ERFs are well suited to mediate the diversity and specificity of ethylene responses through recruiting the desired ethylene-responsive genes (Pirrello et al, 2012). Taking advantage of the recent release of the complete annotated tomato genome sequence (Tomato Genome Consortium, 2012), 77 tomato ERF genes were identified, but knowledge of their physiological significance has been hampered by the functional redundancy among members of this vast gene family.…”
mentioning
confidence: 99%
“…The constitutive expression of several HbERFs led us to consider a post-transcriptional regulation controlling the activity of these proteins. Yet, it has been shown in grapevine, tomato and Arabidopsis as ERF groups (ERF-II, ERF-III, ERF-VII and ERF-IX) were strongly expressed in different tissues (Licausi et al, 2010a;Pirrello et al, 2012;Bailey-Serres et al, 2012). A high abundance transcript in non-stressed condition was potentially a default defence system being present before the stress condition (Cheng et al, 2013b).…”
Section: Potential Post-transcriptional and Posttranslational Regulatmentioning
confidence: 99%
“…Post-transcriptional regulation of Dehydration Responsive Element Binding Proteins 2 (DREB2) genes by alternative splicing has been reported in Arabidopsis, tomato and wheat (Rehman & Mahmood, 2015;Pirrello et al, 2012;Lata & Prasad, 2011;Lucas et al, 2011;Mizoi et al 2012). In the case of alternative splicing, two types of transcripts may exist.…”
Section: Potential Post-transcriptional and Posttranslational Regulatmentioning
confidence: 99%
“…Ethylene synthesis and response-related genes were strongly overrepresented among stem-and, to a lesser extent, primordia-up-regulated genes. This included one 1-aminocyclopropane-1-carboxylate (ACC) synthase (ACS), two ACC oxidases (ACO), and orthologs of eight of the 13 ETHYLENE RESPONSE FACTOR-type ERF/AP2 genes from tomato (Solanum lycopersicum) that were shown to be ethylene responsive (Pirrello et al, 2012;Supplemental Data Set S3). Analysis of earlier time points after onset of flooding indicated that induction of three ethylene signaling-associated genes was fast, within 3 h, and peaked earlier in the primordia (after 3 to 6 h) than in the stem (after 12 to 18 h; Supplemental Fig.…”
Section: Hormone Synthesis and Signaling Pathways Are Affected By Submentioning
confidence: 99%